Genomics of the fetal hypothalamic cellular response to transient hypoxia: endocrine, immune, and metabolic responses - Wood, Charles E. (American Physiological Society, 2013)
Fetuses respond to transient hypoxia (a common stressor in utero) with cellular responses that are appropriate for promoting survival of the fetus. The present experiment was performed to identify the acute genomic responses of the fetal hypothalamus to transient hypoxia. Three fetal sheep were exposed to 30 min of hypoxia and hypothalamic mRNA extracted from samples collected 30 min after return to normoxia. These samples were compared with those from four normoxic control fetuses by the Agilent 019921 ovine array. Differentially regulated genes were analyzed by network analysis and by gene ontology analysis, identifying statistically significant overrepresentation of biological processes. Real-time PCR of selected genes supported the validity of the array data. Hypoxia induced increased expression of genes involved in response to oxygen stimulus, RNA splicing, antiapoptosis, vascular smooth muscle proliferation, and positive regulation of Notch receptor target. Downregulated genes were involved in metabolism, antigen receptor-mediated immunity, macromolecular complex assembly, S-phase, translation elongation, RNA splicing, protein transport, and posttranscriptional regulation. We conclude that these results emphasize that the cellular response to hypoxia involves reduced metabolism, the involvement of the fetal immune system, and the importance of glucocorticoid signaling.